Effect of temperature, oxidation time and substrate: oxidant agent ratio in the yield and composition of humic acids derived from coal, monitored by 1H NMR and FT-ir - Contreras, Eliasara; Leal, Edgardo; Martínez, Manuel (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Véase archivo PDF